Hydrogen-Based Energy Systems for Sustainable Transportation - Matteo Genovese; Francesco Piraino; Petronilla Fragiacomo (Energies)
Rising concerns about climate change, the need to innovate and connect diverse energy sectors, and the challenge of energy dependency are boosting global interest in hydrogen-based technologies [...]